Influence of a programme of professional calibration in the variability of landmark identification using cone beam computed tomography-synthesized and conventional radiographic cephalograms - Delamare, E L (The British Institute of Radiology., 2010)
OBJECTIVES: The validity of any measurement obtained through a cephalogram largely depends on the reproducibility of the cephalometric landmarks. The purpose of this study is to evaluate the influence of a programme of professional calibration (PPC) on the variability of landmark identification comparing conventional radiographs and cone beam CT (CBCT)-synthesized cephalograms. METHODS: 5 graduate students in oral radiology identified 20 cephalometric landmarks from cephalograms generated from conventional radiographs (RADs), Ray-Sum CBCT-synthesized cephalograms (CBTs) and half-skull CBT (HSTs) from 10 patients. After a period of reinforcement on instruction and calibration with inter- and intraexaminer assessment of reproducibility (intraclass coefficient correlation scores > 0.75) for RADs, CBTs and HSTs obtained from 5 different patients, observers were asked to repeat the analysis of the first 10 patients under the same circumstances. Values in millimetres represented each landmark in a table of Cartesian co-ordinates (x- and y-axes). RESULTS: ANOVA showed significant reduction in variability levels after the PPC, and there were no differences among the methods of image acquisition. Repeated measures ANOVA indicated that the PPC accounted for reduction in variability levels in 14 of 20 landmarks. CONCLUSIONS: The results suggest that a PPC has more influence than the type of image acquisition on variability of landmark identification based on two-dimensional cephalometric analysis. Cephalograms obtained from RAD or CBCT can be considered equivalent for clinical and experimental applications.